Paraoxonase-1 and fetuin-A levels in children with cerebral palsy - YÜKSEL, MERAL (My University, 2022)
Background/aim: Studies mostly focused on risk factors and clinical status in children with cerebral palsy (CP). Various antiinflammatory markers may help us in the early diagnosis and clinical classification of cerebral palsy patients. In this study, the relationship between antiinflammatory marker levels and clinical status in patients with CP is determined. It is the first time that Fetuin-A and Paraoxonase-1 (PON-1) are examined in children with CP. Materials and methods: The study is conducted on 79 children which are divided into two groups as CP and control. Gross motor function and spasticity are evaluated in addition to biochemical parameters. Results: There is a statistically significant difference between CP and control group in terms of PON-1 activity, high sensitive C-Reactive Protein, HDL, and total cholesterol levels. There is no statistically significant difference in Fetuin A levels between the two groups. Conclusion: In suspected CP patients less than 24 months of age who possess prenatal and postnatal risk factors, the determination of PON-1 activity can be considered as a biomarker to support early diagnosis.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Aile Sağlığı; Temel Bilgi ve Beceriler; Genel Sağlık Meslekleri; Patofizyoloji; Dahiliye; Değerlendirme ve Teşhis; Tıp (çeşitli); Genel Tıp; Family Practice; Fundamentals and Skills; General Health Professions; Pathophysiology; Internal Medicine; Assessment and Diagnosis; Medicine (miscellaneous); General Medicine; Fetuin-A; paraoxanase-1; cerebral palsy; children; GROSS MOTOR FUNCTION; C-REACTIVE PROTEIN; OXIDATIVE STRESS; RELIABILITY